Arthroscopic Resection Arthroplasty of the Radial Column for SLAC Wrist - Cobb, Tyson K.; Walden, Anna L.; Wilt, Jessica M. (Journal of Wrist Surgery, 2014)
Background Symptomatic advanced scapholunate advanced collapse (SLAC) wrists are typically treated with extensive open procedures, including but not limited to scaphoidectomy plus four-corner fusion (4CF) and proximal row carpectomy (PRC). Although a minimally invasive arthroscopic option would be desirable, no convincing reports exist in the literature. The purpose of this paper is to describe a new surgical technique and outcomes on 14 patients who underwent arthroscopic resection arthroplasty of the radial column (ARARC) for arthroscopic stage II through stage IIIB SLAC wrists and to describe an arthroscopic staging classification of the radiocarpal joint for patients with SLAC wrist.Patients and Methods Data were collected prospectively on 17 patients presenting with radiographic stage I through III SLAC wrist who underwent ARARC in lieu of scaphoidectomy and 4CF or PRC. Fourteen patients (12 men and 2 women) subject to 1-year follow-up were included. The average age was 57 years (range 41 to 78). The mean follow-up was 24 months (range 12 to 61). Arthroscopic resection arthroplasty of the radial column is described for varying stages of arthritic changes of the radioscaphoid joint. Midcarpal resection was not performed.Results The mean Disabilities of the Arm, Shoulder, and Hand (DASH) score was 66 preoperatively and 28 at final follow-up. The mean satisfaction (0 = not satisfied, 5 = completely satisfied) at final follow-up was 4.5 (range 3 to 5). The pain level (on 0–10 scale) improved from 6.6 to 1.3. The total arc of motion changed from 124° preoperatively to 142° postoperatively following an ARARC. Grip was 16 kg preoperatively and 18 kg postoperatively. Radiographic stages typically underestimated arthroscopic staging. Although four of our patients appeared to be radiographic stage I, all were found to have arthritis involving some or all of the radioscaphoid articulation at the time of arthroscopy.Clinical Relevance Pain relief is rapid and remains consistent over time following ARARC. ARARC may be a viable surgical option for patients with SLAC wrist who desire a minimally invasive procedure. Radiographic stages underestimate the degree of arthritic change. Accurate staging requires arthroscopy. The indications and long-term outcome are not well defined; continued surveillance is warranted.Level of Evidence Level IV, Therapeutic study
Keywords: arthritis; arthroplasty; arthroscopic; arthroscopy; minimally invasive; resection; scapholunate advanced collapse; SLAC; wrist